2011
DOI: 10.1016/j.mod.2010.11.005
|View full text |Cite
|
Sign up to set email alerts
|

The floor plate is sufficient for development of the sclerotome and spine without the notochord

Abstract: Danforth'sshort-tail (Sd) mouse is a semi-dominant mutation affecting the development of the vertebral column. Although the notochord degenerates completely by embryonic day 9.5, the vertebral column exists up to the lumber region, suggesting that the floor plate can substitute for notochord function. We previously established the mutant mouse line, Skt(Gt), through gene trap mutagenesis and identified the novel gene, Skt, which was mapped 0.95cM distal to the Sd locus. Taking advantage of the fact that monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…A recent report suggested that the floor plate compensates for notochord function beginning at E10.5(Ando et al, 2011). In these experiments, loss of the notochord at E10.5 did not affect vertebral patterning or Pax1 expression in the sclerotome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report suggested that the floor plate compensates for notochord function beginning at E10.5(Ando et al, 2011). In these experiments, loss of the notochord at E10.5 did not affect vertebral patterning or Pax1 expression in the sclerotome.…”
Section: Resultsmentioning
confidence: 99%
“…In these experiments, loss of the notochord at E10.5 did not affect vertebral patterning or Pax1 expression in the sclerotome. Lack of a notochord at E10.5 should result in the absence of nuclei pulposi, however, the intervertebral discs were not analyzed in mice that lacked a visible notochord(Ando et al, 2011). …”
Section: Resultsmentioning
confidence: 99%
“…Heterozygous and homozygous Sd animals display a broad range of abnormalities in the vertebral column, including reduction or absence of the dens axis, reduction of all vertebral bodies in the dorsoventral axis, split vertebrae, and truncation of the caudal vertebral column [4], [5], [6]. The vertebral columns of Sd/Sd and Sd/+ mice are usually truncated at the seventh thoracic and the sixth caudal vertebral body, respectively [7]. The urogenital system in Sd heterozygotes may display malformations ranging from displaced to missing kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical and genetic manipulations have shown that regional specification of somites depends on secreted factors from the notochord and neural tube (Chiang et al, 1996;Dietrich et al, 1997;Pourquie et al, 1993;Teillet et al, 1998;Teillet and Le Douarin, 1983). Both the notochord and the floor plate produce the morphogen Shh, and its expression in the notochord is essential for induction of the floor plate (Roelink et al, 1994), however, once the floor plate of the neural tube has been established, the notochord is no longer required for vertebral development (Ando et al, 2011). It has recently been shown that Shh is dispensable for vertebral formation after the notochord sheath appears (at approximately E10.0), which is a structure that surrounds the notochord cells, acting as a ''wrapper'' (Choi and Harfe, 2011).…”
Section: Introductionmentioning
confidence: 99%